1980
DOI: 10.1111/j.1399-6576.1980.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Versus General Anaesthesia for Total Hip Arthroplasty in Elderly Patients

Abstract: Sixty elderly patients were given at random either epidural analgesia with bupivacaine 0.75% or general anaesthesia with thiopentone, fentanyl, pancuronium, N2O/O2 for total hip replacement. Preoperatively the patients were of equal physical status with normal and similar laboratory values. All patients were mentally normal for their age. On the 1st postoperative day, the general anaesthesia group had a significantly lower than PaO2 than the epidural group (P less than 0.025). PaO2 in the general anaesthesia g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
2
4

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(76 citation statements)
references
References 14 publications
1
69
2
4
Order By: Relevance
“…The incidence is reportedly between 0% and 26%. Hole et al [37] reported patients receiving general anesthesia showed poorer NP outcome when compared with those receiving epidural anesthesia for THA, but the NP testing in this study was not robust. Only the study by Williams-Russo et al [74] used thorough NP testing and no major differences were seen when comparing the two methods of anesthesia for patients undergoing TKA.…”
Section: Introductioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The incidence is reportedly between 0% and 26%. Hole et al [37] reported patients receiving general anesthesia showed poorer NP outcome when compared with those receiving epidural anesthesia for THA, but the NP testing in this study was not robust. Only the study by Williams-Russo et al [74] used thorough NP testing and no major differences were seen when comparing the two methods of anesthesia for patients undergoing TKA.…”
Section: Introductioncontrasting
confidence: 68%
“…During the past 40 years, many studies have assessed the incidence of these features and attempted to analyze the relationship to the type of anesthesia [6,11,12,37,38,40,51,57,60,64,74]. The incidence is reportedly between 0% and 26%.…”
Section: Introductionmentioning
confidence: 99%
“…The method used by the authors to conceal the allocation sequence was described correctly in four of the studies included. 18,25,27,29 The other studies did not report any details regarding allocation concealment that would make it possible to determine whether this process had been free of bias.…”
Section: Study Validitymentioning
confidence: 99%
“…Thus, 17 articles with the potential to answer our research question were identified. 15,16,18,22,23,25,27,29,30,34,35,[37][38][39]41,42,44 We also analyzed 441 titles from the reference lists of these 17 studies included, but did not find any additional studies (Figure 1). …”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation